2021
DOI: 10.1021/acs.cgd.1c00551
|View full text |Cite
|
Sign up to set email alerts
|

Improving Channel Hydrate Stability via Localized Chemical Tuning of the Water Environment

Abstract: One of the long-standing challenges in working with organic hydrates in general, and channel hydrates in particular, is their propensity to lose water over time and convert (either partially or fully) to anhydrous solid forms. In this work, we demonstrate the ability to rationally increase the thermal stability of a model channel hydrate, the DNA nucleobase thymine hydrate (TH), through the systematic creation of lattice substitutions with 5-aminouracil (AUr). Mixed crystals of TH−AUr with up to 17 mol % AUr w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
(83 reference statements)
0
4
1
Order By: Relevance
“…Nonetheless, such common sense appears not applicable here. We found that the apparent activation energy of solid-state dehydration ($60 kJ mol À1 ) of the UAD phase is significantly lower than the values reported ($70-170 kJ mol À1 ) in the literature (Watts et al, 2021;Takahashi & Uekusa, 2022), which indicates crystal defects may play an important role in the UAD-to-UAA solid-state phase transition. Such defect may be introduced in the growth of UAD crystals at nearly neutral pH (5-6), wherein monovalent tautomer species were suggested to be significant (Fig.…”
Section: Mechanism Of the Core-shell Phase Transitioncontrasting
confidence: 73%
“…Nonetheless, such common sense appears not applicable here. We found that the apparent activation energy of solid-state dehydration ($60 kJ mol À1 ) of the UAD phase is significantly lower than the values reported ($70-170 kJ mol À1 ) in the literature (Watts et al, 2021;Takahashi & Uekusa, 2022), which indicates crystal defects may play an important role in the UAD-to-UAA solid-state phase transition. Such defect may be introduced in the growth of UAD crystals at nearly neutral pH (5-6), wherein monovalent tautomer species were suggested to be significant (Fig.…”
Section: Mechanism Of the Core-shell Phase Transitioncontrasting
confidence: 73%
“…Along with the aromatic zipper, the ionic backbone channel influences overall crystal stability and orientation. [ 52 ] Therefore, the aromatic stacking in F confers enough stability to prevent complete crystal collapse at low RH (which we observe in HYF) but are not so stiff as to prevent such a translation (as in FF). We also speculate that the different critical RH thresholds for F and HYF relate to both the H‐bonding strength of aqueous channels and aromatic deformability.…”
Section: Resultsmentioning
confidence: 89%
“…The structural bracing effect (reminiscent of the behaviour of bulk water on freezing) that occurs between −60 °C and −70 °C is probably brought about by non-lattice ordering of the water in T1-R on cooling, which also inhibits the transfer of water to the surroundings. Indeed, it is known that the dehydration temperature of a channel hydrate depends on the level of geometric frustration imposed on the included water by the host framework 29 . That water can flow within the crystal at temperatures above −70 °C is probably due to a mismatch between the geometry of the channel (that is, its diameter and the locations of the exposed hydroxyl groups) and a hypothetical long-range ordered ice-like structure 30 .…”
Section: Dehydration At Subglacial Temperaturesmentioning
confidence: 99%